Investigation of the effect of simultaneous use of silver diamine fluoride and potassium iodide on the shear bond strength of total etch and universal adhesive systems to dentin - Farnaz Farahat; Abdolrahim Davari; Haleh Karami (Wolters Kluwer Medknow Publications, 2022)
Background: Applying silver diamine fluoride (SDF) is recommended to arrest and prevent dental caries. However, it may jeopardize the bond of the restorative materials to the tooth. The aim of the present in vitro study was to evaluate the effect of the simultaneous use of the SDF and potassium iodide (KI) on shear bond strength to the sound dentin. Materials and Methods: In this in vitro study, on the buccal and lingual surfaces of the 48 human third molar teeth, dentinal surfaces with a diameter of 6 mm were created by removing the enamel. Then, the specimens were divided into four groups based on applying or not applying the KI/SDF and adhesive type (etch and rinse [E and R] or universal adhesive). Afterward, cylindrical composite restoration was made on the surfaces. Half of the specimens were subjected to 1000 cycles of thermocycling. Subsequently, the shear bond strength was evaluated by Universal testing machine. Furthermore, the type of failure was determined by a stereomicroscope. Data were analyzed by t-test and Chi-square at a significance level of P < 0.05. Results: There were statistically significant differences in shear bond strength between Groups 1 and 3 (P < 0.05), whereas the bond strength difference between Groups 2 and 4 was not statistically significant (P = 0.609). Failures were predominantly of the mixed type in almost all groups. Conclusion: Based on the results of this study, the superiority of shear bond strength of universal adhesive to the sound dentin compared to E and R adhesive was confirmed. Thus, using this type of adhesive is recommended under the condition that KI/SDF anticaries material is applied.